Distribution of Mosquitoes Along Wadi El-Rayan Protected Area (Journal of Nuclear Technology in Applied Science, 2019)
The knowledge of mosquito distribution in any environment is very important to control and avoid their effect on humans and animals. For this purpose, the present study was designed to monitor the mosquito distribution and abundance along Wadi El‐Rayan Protected Area Fayoum Governorate. Throughout the four seasons from winter 2017 to autumn 2018, 10 mosquito species were recorded during this study belong to two genera. Culex was the most abundant genus and comprised 4 species representing 88.01% of the total mosquito count and Anopheles represented by 6 species (11.99% of the total mosquito count). Culex pipiens was the major dominant and common species followed by Culex antennatus and Culex bivittatus while Anopheles multicolor and Anopheles tenebrosus were the rarest mosquito species. Mosquito abundance was varied seasonally and flourished in summer, while it declines during winter. On the other hand, the mosquitoes were well distributed among study sites, but it was highly abundant at site 2 and low at site 4. The diversity indices and species richness are narrow ranged among the surveyed site, which indicates the stability of the mosquito community in the protectorate.
Keywords: Mosquitoes; Abundance; diversity; Wadi El‐Rayan Protected Area